HR sajátosságok feltárása vezetői mélyinterjúk alapján megváltozott munkaképességű személyeket foglalkoztató szevezeteknél - Dajnoki, Krisztina (Közép-Európai Közlemények, 2014)
By joining the European Union problems of cases of disability and equality have become central issues. In Hungary the employment rate of people with disabilities is low. In order that the labour market (re)integration be successful we need to learn about the employers’ expectations and the characteristics of the employees concerned. The aim of this article is to highlight by the citing of deep-interviews how the leaders of the different types of organisations with different activities see the employment of people with disabilities and what HR characteristics need more attention. We included in the research HR experts and employers who have already employed people with disabilities and thus can provide a positive example for other employers. Furthermore the research shows how the leaders of foundations who are in contact with people with disabilities and leaders of advocacy organisations see the employment of the group concerned. This research was realized in the frames of TÁMOP 4.2.4. A/2-11-1-2012-0001 „National Excellence Program – Elaborating and operating an inland student and researcher personal support system” The project was subsidized by the European Union and co-financed by the European Social Fund.